Analysis of Double Jobs in the Secretariat of the Sidoarjo Regency General Election Supervisory Agency - Nur Aini Fatjeriyah; Indira Arundinasari (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Bawaslu is an institution tasked with supervising and ensuring that elections run in accordance with election criteria and rules. In this case, the Sidoarjo Regency Bawaslu Secretariat has a crucial role in supporting administration, operations and technical support in carrying out its duties and responsibilities in elections in the Sidoarjo Regency area. Thus, Bawaslu is required to have an effective and efficient structure because Bawaslu's structure can influence general elections. However, in reality there are still double jobs within the secretariat of the Sidoarjo Regency General Election Supervisory Agency. It is hoped that the findings from this research will provide clarity on the problem of double jobs within the Bawaslu Secretariat of Sidoarjo Regency. The research was conducted using qualitative methods and data collection techniques were carried out through observation and interviews. The results of this research show that double work is not a problem but rather a solution to the Bawaslu moratorium period to overcome the shortage of human resources by using effective and efficient work patterns.  Keywords: Bawaslu, double job, moratorium